Mobile Application for Promoting Orang Asli Product (Product Asli) - Zakaria, Nur Haryani; Jin, Tan Eu; Mat Aji, Zahurin; Awang, Hapini; Mohd Khalid, Al Hanisham (Multidisciplinary Applied Research and Innovation, 2023)
Orang Asli (OA) in Malaysia could produce many high-quality products, but the products they made cannot be sold. This is due to the lack of platform to promote or sell the products. The aim of this project is to create a platform which is a mobile based platform which specifically used to promote OA products. Aligned with the technological advancement these days, majority of consumers are shopping online or even do some searching on the Internet before going to physical store to buy. In addition, in this pandemic era of Covid-19, many having business done in online platform is no longer regarded as competitive advantage but is considered necessity. Thus, creating a mobile application would be a good solution to this problem. By resolving this problem, we could help OA to generate income from their own products and increase the exposure of technology and ICT skills among them.